Quantitative Fluorescence In Situ Hybridization (FISH) of Magnetically Confined Bacteria Enables Early Detection of Human Bacteremia. Issue 3 (3rd February 2022) - Lee, Min Seok; Hyun, Hwi; Park, Inwon; Kim, Sungho; Jang, Dong‐Hyun; Kim, Seonghye; Im, Jae‐Kyeong; Kim, Hajin; Lee, Jae Hyuk; Kwon, Taejoon; Kang, Joo H.
Abstract: The current diagnosis of bacteremia mainly relies on blood culture, which is inadequate for the rapid and quantitative determination of most bacteria in blood. Here, a quantitative, multiplex, microfluidic fluorescence in situ hybridization method (μFISH) is developed, which enables early and rapid (3‐h) diagnosis of bacteremia without the need for prior blood culture. This novel technology employs mannose‐binding lectin‐coated magnetic nanoparticles, which effectively opsonize a broad range of pathogens, magnetically sequestering them in a microfluidic device. Therein, μFISH probes, based on unique 16S rRNA sequences, enable the identification and quantification of sequestered pathogens both in saline and whole blood, which is more sensitive than conventional polymerase chain reaction. Using μFISH, Escherichia coli ( E. coli ) is detected in whole blood collected from a porcine disease model and from E. coli ‐infected patients. Moreover, the proportion of E. coli, relative to other bacterial levels in the blood, is accurately and rapidly determined, which is not possible using conventional diagnostic methods. Blood from E. coli ‐infected patients is differentiated from healthy donors' blood using cutoff values with a 0.05 significance level. Thus, μFISH is a versatile method that can be used to rapidly identify pathogens and determine their levels relative to other culturable and nonculturable bacteria in biological samples. Abstract : For early detection of bacteremia, a new diagnostic platform is developed using fluorescence in situ hybridization in a microfluidic device (μFISH). Pathogens in bacteremic blood are enriched by recombinant human mannose‐binding lectin‐coated magnetic nanoparticles (rhMBL‐MNP) and magnetically captured in the μFISH device. The FISH‐labeled bacteria are fluorescently visualized and quantified.